Thailand’s Rice Conundrum: Time for Economic Restructuring - Pitakdumrongkit, Kaewkamol (2016)
Thai farmers have been witnessing the rice price plunge which further hurt their income and living standards. The government’s measures to alleviate their plight have been quick fixes at best. It must come up with a longer term plan to tackle the bigger issue of economic restructuring.